A new species of the Bokermannohyla circumdata group (Amphibia: Anura: Hylidae) from Chapada Diamantina, State of Bahia, Brazil - Napoli, Marcelo F.; Juncá, Flora A. (Zootaxa, 2006)
A new species of the Bokermannohyla circumdata group, B. diamantina sp. nov., is described from Serra dos Barbados, Municipality of Abaíra, State of Bahia, Brazil. This locality belongs to Chapada Diamantina, a semiarid region in central Bahia. This is the first record of a species of the B. circumdata group from the Brazilian semiarid. Bokermannohyla diamantina is diagnosed by the medium size (snout-vent length 47.0–51.7 mm in adult specimens); head length 2.8–2.9 times smaller than snout-vent length; tympanum medium-sized, its diameter 1.3–1.5 times smaller than eye diameter (tympanum diameter/snout-vent length 0.07); thigh and tibia lengths 0.48–0.52 and 0.49–0.51 of snout-vent length, respectively; dorsum medium to blackish brown, with weak transverse dark brown bars; flanks, anterior, and posterior surfaces of thighs with dark transverse brown stripes, lacking additional thin stripes between them; distinct vocal slits in adult males; advertisement call with 2–4 notes, and dominant frequency from 0.39–0.56 kHz.